Strategi Pengelolaan Sampah di Kota Mojokerto dalam Perspektif Analisis Strengths, Opportunities, Aspirations, Results - Bella Wanda Anastasia; Lukman Arif (Mahesa Research Center, 2022)
This study aims to identify and describe the SOAR Analysis Model in the Waste Management Strategy at the Mojokerto City Environmental Service. The problem in this study is focused on an increase in the amount of waste generation which has implications for the performance of the Mojokerto City Environmental Service as a regional work unit authorized in the implementation of waste management. The research method used in this research is a qualitative research method with a descriptive approach. The theory used is the SOAR analysis from Stavros & Hinrichs (2009) which was identified based on the components of the waste management subsystem. The results showed that the SOAR analysis model in the waste management strategy at the Mojokerto City Environmental Service had been implemented but was not maximal enough, especially in the financing aspect which affected the operational speed of waste management. However, in terms of institutional, regulatory, community participation, and technical operations, the best efforts have been shown to generate positive energy in achieving effective waste management in Mojokerto City.